2017
DOI: 10.1155/2017/9352618
|View full text |Cite|
|
Sign up to set email alerts
|

Experiment on Seepage Property and Sand Inrush Criterion for Granular Rock Mass

Abstract: Water and sand inrush is one of the most serious threats in some shallow coal mines in China. In order to understand the process of sand inrush, experiments were performed to obtain the criterion for sand inrush. First, seepage tests were carried out to study the hydraulic properties of granular sandstone. The results indicate that seepage velocity has a linear relation with the porosity and particle-size distribution parameter. Then, sand inrush tests were conducted to investigate the critical conditions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…In recent years, a large number of tunnels have been constructed in unfavorable geology such as completely weathered granite, karst, and fault [1][2][3][4], causing various challenges to the geotechnical engineers, for example, collapse [5], land subsidence [6], groundwater inflow [7,8], and total environmental hazards [9]. The completely weathered granite, one of the typical unfavorable geologies, is widely distributed in subtropical, tropical, and humid temperature zones [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a large number of tunnels have been constructed in unfavorable geology such as completely weathered granite, karst, and fault [1][2][3][4], causing various challenges to the geotechnical engineers, for example, collapse [5], land subsidence [6], groundwater inflow [7,8], and total environmental hazards [9]. The completely weathered granite, one of the typical unfavorable geologies, is widely distributed in subtropical, tropical, and humid temperature zones [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Walsh [28] and Wang et al [29] studied the permeability under different water pressures and confining pressures. Moreover, many researches showed that the critical conditions existed for water inrush, such as water pressure and excavation thickness [4,30].…”
Section: Introductionmentioning
confidence: 99%
“…e velocity is calculated by the simultaneous Equations (6), (14), and (20), Equations (6), (15), and (20), Equations (6), (16), and (20), and Equations (17) and (20) when the sandwater mixture ow is, respectively, in laminar ow, e ectively smooth ow, transition region, and rough ow. e calculation results are shown in Table 7, from which it can be known that the sand-water mixture ow belongs to transition region, and the velocity and volume are 15.32 to 17.78 m/s and 310,000 to 350,000 m 3 , respectively.…”
Section: E Calculation Of Computing Methodmentioning
confidence: 99%
“…When the mining depth is shallow, the mininginduced fractures may go through the rock layers to the sand bed, or even to the ground surface. In this situation, the water and sand can move to the goaf through the fractures and granular rock mass, which results in the quicksand disaster [14]. Secondly, the quicksand disaster caused by a borehole from ground surface to underground.…”
Section: Introductionmentioning
confidence: 99%
“…Water-sand inrush is a most serious mine disaster in western China, particularly in the Shaanxi province, the major energy resource centre of China [1,2]. The typical geological characteristics of the coal mines in this area provide the conditions for the occurrence of water-sand inrush.…”
Section: Introductionmentioning
confidence: 99%